Disability and Electoral Justice for Inclusive Participation - Putra Perbawa, Ketut Sukewati Lanang; Paul Atagamen Aidonojie; Benjamin Okorie Ajah (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
The political participation of people with disabilities is crucial to achieving an inclusive and equitable democracy. Although Indonesia has recognized the political rights of people with disabilities through various regulations, the implementation of these rights still faces significant structural barriers and systemic discrimination. This research aims to analyze the practice of electoral justice for people with disabilities in Indonesia by learning from the experience of South Africa, which has built a comprehensive and inclusive legal framework and election policy. The research method used is normative juridical, with a qualitative comparative study analyzing legal documents, election policies, and implementation practices in both countries. The research results show that, First, Indonesia has recognized the political rights of people with disabilities through various regulations. However, realizing these rights is still far from optimal due to structural, administrative, and social barriers. Second, South Africa has implemented an effective accessibility policy and involved the Independent Electoral Commission (IEC) in advocacy, voter education, and provision of supporting facilities, thus facilitating the full participation of people with disabilities in the political process. Third, more specific legal and policy reforms are needed, as well as increasing the capacity and commitment of election organizing institutions to realize electoral justice that ensures inclusive and meaningful political participation for people with disabilities in Indonesia. This can be done by amending election laws, improving the substance to protect the political rights of people with disabilities, and strengthening institutions such as the General Election Commission and the Election Supervisory Body regarding supervision.